Faktor-Faktor yang berhubungan dengan Turnover Intentions Tenaga Kesehatan di Puskesmas Hialu Kabupaten Konawe Utara - Tomalili, Herniawati; Risky, Sartini (Jurnal Gizi Ilmiah, 2017)
Turnover intentions are defined as the individual's desire to leave organization and look for alternative jobs. Based on the data obtained information that during the period 2013 to 2015 the turnover rate the intentions of health workers are quite high at the Hialu Health Center. Based on Data Secondary in 2013 there were 8 health workers who left their work with details of 5 midwives, 3 nurses, in 2014 there were 8 health workers with details of 4 midwives, 4 nurses, and in 2015 there were 11 health workers who left their jobs with details of 2 midwives, 4 nurses,1 Analysts, 1 Public Health Personnel, 1 Administration Staff, and 2 Doctors for various reasons. This study aims to determine the factors that related to the Turnover Intentions of health workers at the Hialu Health Center, North Konawe district. This type of research is a quantitative study with a cross sectional study design. The sample in this study amounted to 48 respondents. The research hypothesis was tested using the Chi Square test to determine the effect between the independent variable and the dependent variable. The results of this study indicate that there is a moderate relationship between Organizational Commitment and Turnover Intentions of health workers at the Hialu Health Center, North Konawe Regency. Hialu Public Health Center, North Konawe Regency X2Count 11,822 > X2Table 3,841, There is a strong relationship between job satisfaction and employee turnover Health at the Hialu Health Center, North Konawe Regency. X2Count 13.986 > X2Table 3.841. The author suggests that the attitude of the Puskesmas leadership as a friend and friend, giving appreciation for the work achieved, being wise in acting and encouraging subordinates to come forward and listen to the opinions of subordinates, because this can increase job satisfaction